Spatial production distribution, economic viability and value chain features of teff in Ethiopia: Systematic review - Esubalew Tadele; Tewabe Hibistu (Cogent Economics & Finance, 2022)
Teff is the most preferred and most commercialized cereal crop in Ethiopia. it's one of the underutilized crops. It's nutrient-dense and well-suited to Ethiopia's growing conditions, but little has been invested to tap into its domestic and international markets. This review focus on the regional teff production distribution, economic significance, and value chain of teff in Ethiopia. The country has a chance in teff specialization and value-added products will likely contribute to generating more incomes, reduce poverty and sustain growth. But unable to overcoming of constraints and seizing opportunities associated with the value chain and its components. Mainly due to teff producing and value addition practice is insufficient and generally depends on conventional practices, and its marketplace is restricted local and the government imposes an export ban on it to limit the upward pressure on domestic grain prices and address local food security. Hence, in a nutshell, value chain development aimed at stimulating economic growth and increasing competitiveness is a vital issue. To take advantage of growing domestic and international demand for teff, the domestic teff industry must invest heavily in improving teff production methods, opening up and expanding its international market to ensure its status as a superglobal food and a contributor to global food security gains. This needs simultaneously investments and policy support networks, which are coordinated with all relevant stakeholders.
Keywords: 330; teff spatial production; economic viability; value chain; food and nutrition security and future demand